ANALISIS BEBAN KERJA ANTARA BELLBOY DAN FRONT DESK AGENT DI SWISS-BELHOTEL HARBOUR BAY BATAM - Clement Ananto; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to determine the right number of employees which are Bellboy and Front Desk Agent ideal workload handled at Swiss-Belhotel Harbour Bay Batam.This research uses descriptive quantitative method for examining the raised issues. The sample in this research are 11 people and using census method. Data collection techniques in this study using observation, interviews and documentation. By using the exponent determinants technique (exponential smoothing), with two exponents in the human resources planning which consists of exponents workload in producing a product, as an analysis of the workload (work load analysis) and exponent of time (cycle time) to complete a product and to find the number of employees or staff that were ideal.Based on the research that has been done, for the whole of the results and from the calculation of ideal working time for the Bellboy still need 4 people, and 3 people for a Front Desk Agent, that number must be filled by Swiss-Belhotel Harbour Bay Batam to cover their staff workload.Keywords: Workload, Bellboy, Front Desk Agent, Number of Ideal Employees, Swiss-Belhotel Harbour Bay Batam